Entre passos, traços e pinceladas: articulações de Margaret Mee com os cânones da ilustração botânica - Guerino, Lydia Varela (2021)
Margaret Mee was an English artist who painted Brazilian flora in her expression of botanical art. Her works and trajectory were researched and analyzed from the perspectives of art history, biology and botanical dissemination. The objective of this work is, within the context of science, technology and society, to identify and highlight cracks, contradictions and even continuities, which are the result of the artist’s negotiation with the canons and techniques of botanical illustration, the area where she worked and materialized her work. To reach this objective, we will first use a bibliographic and pictorial research methodology, together with a specific methodology for the analysis of images. Chapter 1 will identify and contextualize five main canonical categories for botanical illustration and; in addition the problematization through sociotechnical codes which involve artistic processes and their historical-cultural surroundings. In chapter 2 we will discuss Margaret Mee’s life and work, narrating her trajectory. Still in this chapter, we will identify the cracks and also, in a contradictory way, continuities based on canons and technical codes. Chapter 3 will show evidence of the cracks, contradictions and continuities materialized in two of her works. The analysis methodology used for this evidence and discussion will be: the identification of the canonical categories of botanical illustration, followed by the sócio-technical reading in each of the chosen works. Through the analysis of these works, we seek to make explicit the artist’s negotiation between her political stance and the canons she learned in her experience as a Botanical Illustrator. Through the identification of the artist’s deviations from the canons, it will be possible to perceive voices that go beyond the represented image, that (re) educate us in the way of sócio-technical look at specimens and nature – especially from the Amazon Region.